Reformatting palivizumab and motavizumab from IgG to human IgA impairs their efficacy against RSV infection in vitro and in vivo. Issue 3 (3rd April 2018) - Jacobino, Shamir R.; Nederend, Maaike; Reijneveld, J. Frederiek; Augustijn, Daan; Jansen, J. H. Marco; Meeldijk, Jan; Reiding, Karli R.; Wuhrer, Manfred; Coenjaerts, Frank E. J.; Hack, C. Erik; Bont, Louis J.; Leusen, Jeanette H. W.
ABSTRACT: Respiratory syncytial virus (RSV) infection is a leading cause of hospitalization and mortality in young children. Protective therapy options are limited. Currently, palivizumab, a monoclonal IgG1 antibody, is the only licensed drug for RSV prophylaxis, although other IgG antibody candidates are being evaluated. However, at the respiratory mucosa, IgA antibodies are most abundant and act as the first line of defense against invading pathogens. Therefore, it would be logical to explore the potential of recombinant human IgA antibodies to protect against viral respiratory infection, but very little research on the topic has been published. Moreover, it is unknown whether human antibodies of the IgA isotype are better suited than those of the IgG isotype as antiviral drugs to combat respiratory infections. To address this, we generated various human IgA antibody formats of palivizumab and motavizumab, two well-characterized human IgG1 anti-RSV antibodies. We evaluated their efficacy to prevent RSV infection in vitro and in vivo and found similar, but somewhat decreased efficacy for different IgA subclasses and formats. Thus, reformatting palivizumab or motavizumab into IgA reduces the antiviral potency of either antibody. Moreover, our results indicate that the efficacy of intranasal IgA prophylaxis against RSV infection in human FcαRI transgenic mice is independent of Fc receptor expression.